The Administration and Realization of Estate in Corporate Bankruptcy Proceedings - Jokubauskas, Remigijus (Teisė, 2019)
This article analyzes estate administration and realization as well as the concept of estate in bankruptcy proceedings. It also analyzes which methods of estate realization are established in bankruptcy law, and which of them allow selling estate faster. The article evaluates how courts ensure the effective realization of estate in bankruptcy proceedings.